4.5k views
3 votes
Tor: Convert f(x) = 3(x-4)^2 + 3 to standard form. Explain/Show how you did it.

User TehSphinX
by
5.5k points

1 Answer

6 votes

Answer:

f(x) = 3(x-4)^2 - 33

Explanation:

To convert the function f(x) = 3(x-4)^2 + 3 to standard form, we need to complete the square.

First, we can rewrite the function as follows:

f(x) = 3x^2 - 24x + 36 + 3

Then, we need to add and subtract (24/2)^2 = 36 to complete the square:

f(x) = 3x^2 - 24x + 36 + 3 + 36 - 36

= (3x^2 - 24x + 36) + 3 - 36

= (3(x-4)^2) + 3 - 36

So, the standard form of the function is:

f(x) = 3(x-4)^2 - 33

This is the final form of the function.

User Hessuew
by
5.2k points